Todor Cepreganov (ed.), History of the Mecedonian People, Aneta Shukarova – Mitko B. Panov – Dragi Georgiev – Krste Bitkovski – Ivan Katardziev – Vanche Stojchev – Novica Veljanovski – Todor Cepreganov (authors), Skopje, Institute of National History, 200 - Σφέτας Σπυρ. (Μακεδονικά, 2011)
no abstract